Immune checkpoints in chronic obstructive pulmonary disease - Tom M.A. Wilkinson (European Respiratory Review, 2017)
Cell-mediated immune responses are vital to the body's defence against infection and play a key role in tumour immunity. T-cell activation and cytotoxic function is tightly regulated by a series of immune-regulatory receptor–ligand interactions or immune checkpoints. These controls limit immune-mediated damage, particularly in the context of chronic infection. However, prolonged signalling through these axes can lead to progressive loss of T-cell function, termed exhaustion. Understanding of the biology of checkpoints and that exhaustion is reversible has been key to the development of new therapies directed at reversing the dysfunctional status of T-cells, which are dramatically improving outcomes of cancer treatment. Emerging data suggest that immune checkpoint axes are dysregulated in chronic obstructive pulmonary disease (COPD). T-cells from diseased lungs express the key receptor programmed death (PD)1 and demonstrate loss of cytotoxic function. However, the picture is complex with evidence of downregulation of the associated ligand PDL1 on alveolar macrophages. The resulting impact may be excessive T-cell inflammation as a consequence of acute infection, which may contribute to the pattern of exacerbation and lung damage characteristic of COPD. More work is needed to understand these immune controls in COPD before the therapeutic advances seen in lung cancer can be explored.